Decentring empire : Britain, India, and the transcolonial world - Durba Ghosh(Editor) Dane Kennedy(Editor) (New perspectives in South Asian history, 2006)
Contributed articles on historiography of British colonies in the world and India presented earlier at a conference held at University of California, Berkeley in April 2003.